Behavioral public choice: a survey - Schnellenbach, Jan; Schubert, Christian (Freiburger Diskussionspapiere zur Ordnungsökonomik, 2014)
Public choice theory has originally been motivated by the need to correct the asymmetry, widespread in traditional welfare economics, between the motivational assumptions of market participants and policymakers: Those who played the game of politics should also be considered rational and self-interested. History repeats itself with the rise of behavioral economics: Cognitive biases discovered in market participants often induce a call for rational governments to intervene. Recently, however, behavioral economics has also been applied to the explanatory analysis of the political process. This paper surveys the current state of the emerging field of “behavioral public choice” and considers the scope for further research.
Keywords: Arbeitspapier; Graue Literatur